Scale effects on the performance of sawtooth spoilers in transonic rectangular cavity flow - Saddington, Alistair J.; Knowles, Kevin; Thangamani, Varun (Springer, 2015)
An experimental study was conducted on the effectiveness of sawtooth spoilers at suppressing acoustic tones within a rectangular cavity with a length-to-depth ratio of five and a width-to-depth ratio of two, operating at a freestream Mach number of 0.71. Whereas previous research has focussed on the ratio of spoiler height to boundary-layer thickness (h/δ), this study also considers the effect of the ratio of cavity length to boundary-layer thickness (L/δ). Using a combination of unsteady pressure measurements and particle image velocimetry, it was established that consideration of the magnitude of both parameters is important when designing passive control methods for transonic cavities. A correlation was developed which suggests that in order to suppress fully the cavity tones, a critical spoiler height, h cr, is defined such that h cr/δ = 0.065 ≤ L/δ ≤ 0.082.
Keywords: Particle Image Velocimetry; Shear Layer; Particle Image Velocimetry Measurement; Broadband Noise; Particle Image Velocimetry Data